Seed germination ecology of Portulaca oleracea L.: an important weed of rice and upland crops - Chauhan, B.S.; Johnson, D.E. (Wiley, 2009)
Portulaca oleracea, a C4 species, is reported to be a serious weed in 45 crops in 81 countries. Experiments were conducted in the laboratory, the screenhouse and the field to determine the influence of environmental factors on seed germination and seedling emergence of P. oleracea. In the laboratory, germination in the dark was low and was not influenced by the tested temperatures (35/25°C, 30/20°C and 25/15°C alternating day/night temperatures). In the light/dark regime, however, germination was lower at 25/15°C and 35/25°C than at 30/20°C (70%, 75% and 81% germination, respectively). In conditions of 106 mM sodium chloride or −0.34 MPa osmotic potential, seeds germinated to only 50% of maximum germination of the control. Germination was not influenced by buffered pH solutions ranging from 5 to 9. In the screenhouse, germination was greatest for seeds placed on the soil surface, but emergence declined with increasing seed burial depth in soil; no seedlings emerged from the depth of 2 cm. Seedling emergence and seedling dry matter were markedly reduced by the addition of rice residue to the soil surface at rates equivalent to 4 to 6 t ha−1. In the field, seedling emergence of P. oleracea was greater under zero till (ZT) (17–20%) than under minimum tillage (6–10%), a likely reflection of low seed burial and exposure of seeds to light with a ZT system. This study identifies some of the factors enabling P. oleracea to be a widespread weed in the humid tropics, and the information could contribute to improved control strategies.